2011
DOI: 10.1038/ki.2011.287
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxaluria: a gut–kidney axis?

Abstract: Hyperoxaluria leads to urinary calcium oxalate (CaOx) supersaturation, resulting in the formation and retention of CaOx crystals in renal tissue. CaOx crystals may contribute to the formation of diffuse renal calcifications (nephrocalcinosis) or stones (nephrolithiasis). When the innate renal defense mechanisms are suppressed, injury and progressive inflammation caused by these CaOx crystals, together with secondary complications such as tubular obstruction, may lead to decreased renal function and in severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
170
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 173 publications
2
170
2
3
Order By: Relevance
“…[23][24][25] However, the precise molecular mechanisms that result in hyperoxaluria as a consequence of defective 4-hydroxyproline catabolism due to HOGA1 mutations remain unknown, as much as the pathogenesis and the significance of hypercalciuria. Riedel and colleagues 22 demonstrated that in contrast to related bacterial enzymes termed DHDPS human HOGA1 favours forward cleavage of 4-hydroxy-2-oxo-glutarate to glyoxylate and pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] However, the precise molecular mechanisms that result in hyperoxaluria as a consequence of defective 4-hydroxyproline catabolism due to HOGA1 mutations remain unknown, as much as the pathogenesis and the significance of hypercalciuria. Riedel and colleagues 22 demonstrated that in contrast to related bacterial enzymes termed DHDPS human HOGA1 favours forward cleavage of 4-hydroxy-2-oxo-glutarate to glyoxylate and pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate nephropathy is a rare cause of acute and chronic renal failure (1)(2)(3)(4). Oxalate accumulation in renal allografts may arise de novo, or as "recurrence" of native kidney disease if underlying hyperoxalosis remains uncorrected.…”
Section: Introductionmentioning
confidence: 99%
“…Primary hyperoxaluria is a hereditary condition with at least three different genetic enzymatic defects ( Table 1) (1). Currently, liver or combined liver-kidney transplantation is recommended for patients with primary hyperoxaluria, with liver transplantation serving to correct the enzymatic deficiency (1). Secondary hyperoxaluria can arise from a variety of different processes (Table 1), including iatrogenic causes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations